High Efficient and Environment Friendly Plasma-Enhanced Synthesis of Al2O3-Coated LiNi1/3Co1/3Mn1/3O2 With Excellent Electrochemical Performance - Wang, Xinzhi; Jiang, Qianqian; Zhang, Yichi; Yuan, Nannan; Tang, Jianguo (Frontiers in Chemistry, 2020)
PLA-1-Al2O3@LNCM synthesized from efficient and facile plasma-enhanced method exhibits markedly improved capacity retention with 98.6% after 100th cycles, which is much larger than that of LNCM with 80% after 100 cycles. What’s more, it also exhibit signiﬁcantly enhanced cyclability compared to that of 1-Al2O3@LNCM cathodes prepared form the normal solid state method, which further illustrates the efficiency and superiority of this plasma-enhanced method. More importantly, the rate performance of PLA-1-Al2O3@LNCM is improved because of the better electrolyte storage of the assembled hierarchical architecture of the Al2O3 coating layer aﬀording unimpeded Li+ diﬀusion from electrode to electrolyte. When cycling at 55 °C, the PLA-1-Al2O3@LNCM shows 93.6% capacity retention after 100 cycles, which is greatly enhanced due to the uniform Al2O3 layer. Meanwhile, growth of polarization impedance during cycling can be effectively suppressed by Al2O3 layer, which can further confirm the effect Al2O3 layer coated on the surface of the LNCM. The enhanced cycling performance and thermal stability can illustrate this facile surface modiﬁcation using the plasma-enhanced method can form eﬀective structure of coating layer, which indicates its great application prospects in the modification on other electrode materials.